Implementation Mapping of Integrated Cost Management Concepts with the Phases of Product Development - Basuki, Satrio Samudro Aji; Tirkaamiana, Dean (Future Science / FSH-PH Publications, 2024)
The alteration in the business environment is always dynamic, and the companies must respond to these issues. It is necessary for the management to always be conscious of the prevailing condition, especially in the cost aspect. Cost aspect is substantial for profit-oriented companies to lead to the profit as optimum as possible. Therefore, the cost management is requisite in order to manage cost in the proper manner. Cost management is considered as one of the essential tools to enhance the competitiveness of business potential. Through a well-defined cost management system, man-agement is capable to acquire accurate information which pro-spective to be exploited for decision-making instruments and con-trol the internal business process entirely. Many studies have been conducted to provide a more appropriate and proper cost man-agement system for the companies. The current development in-cludes integrating cost management with Kaizen, Target Cost Modeling, Target Value Design, Cost Effectiveness Analysis, and even with the Monte Carlo Simulation in order to accommodate the uncertainty factor in the cost. Therefore, this paper provides an overview related to the cost management implementation by mapping those current development into the modified Generic Product Development framework.